Enabling a community of practice: participatory practices in building a water-sensitive catchment - Bennett, Andrew (Department of Environmental and Geographical Science, 2025)
This study explores the conditions for an enabling environment that lends itself to a more inclusive, relational, value-framing approach to nature and biodiversity in the field of urban water management. There are increasing calls in water governance for a better understanding of how participatory processes can be designed and structured to accommodate a range of stakeholders and achieve sustained public value. Although local governments are making progress in establishing formal community participation strategies, the overall engagement undertaken often informs citizens rather than involving them, thus limiting the input from different actors. Literature suggests that by fostering landscapes of communities of practice (CoPs), governments can enable more effective cooperation, interrelationships, and datadriven feedback loops between public authorities and communities that leads to effective policy- and decision-making. In CoPs theory, the notion of a ‘community' does not refer to the traditional sense of a friendly, harmonious, and bounded group but rather expresses the strength of voluntary, informal, authentic relationships between participants where a sense of belonging is an accomplishment. The rise of CoPs also reflects new societal dynamics in which citizens are more willing and able to be involved in or initiate the processes of policy formulation, implementation, and service delivery. Drawing on the work of the Friends of Liesbeek (FOL) - a community-based organisation (CBO) stewarding the Liesbeek River in Cape Town for over 30 years - the overall aim of this research was to understand how a CoP is initiated, developed, and sustained. The research design was a deductive thematic analysis, using social learning and CoPs theory to interpret the engagements and activities of FOL. The study attempts to show how the natural relational process of social learning spaces (CoPs) can improve the effectiveness of participation across different scales and sectors (from local to global) in the water domain. Although not without its limitations, a CoPs approach offers the potential to address complex water challenges by overcoming situations where state and nonstate actors continue to work independently from each other and do not sufficiently share, adopt, and implement solutions that work in practice and can be replicated at scale. Examples of CBOs, such as FOL, illustrate that ordinary citizens can and do play a critical role in managing water resources at local level and shaping water governance and policy.